Analyzing the Resilience of Farming Households in Upland Areas - Aubrey D. Tabuga; Anna Rita P. Vargas; Madeleine Louise S. Bai\~no (Philippine Institute for Development Studies (PIDS), 2023)
The challenges faced by farming communities, such as typhoons, floods, droughts, volcanic eruptions, and pest infestations, can pose significant costs on their livelihoods. This study examines the resilience of upland farming households using a small yet novel survey conducted in the municipality of Atok in Benguet. To analyze resilience, the study explores indicators based on the conceptual framework put forward by Schipper and Langston (2015), namely learning, options, and flexibility. Principal Components Analysis (PCA) was applied for index creation, while ordered logistic regression was employed to assess recovery levels of farming household. The findings show that factors contributing to the learning dimension of resilience include wealth/assets, strategic positioning within social networks, and access to transportation, proxied by vehicle ownership. The study recommends targeted interventions for households in lower-income brackets, peripheral network positions, and those lacking their own means of transportation, especially focusing on enhancing learning capacities.
Keywords: 330; Resilience; upland farming; recovery; agricultural sector